2007
DOI: 10.1097/01.sla.0000225093.58071.c6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Outcomes Between Open and Minimally Invasive Esophagectomy

Abstract: Minimally invasive techniques to resect the esophagus in patients with cancer were confirmed to be safe and comparable to an open approach with respect to postoperative recovery and cancer survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
285
2
27

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 351 publications
(342 citation statements)
references
References 28 publications
28
285
2
27
Order By: Relevance
“…Lymph node harvest was not reported by Luketich et al 13 . Smithers and colleagues 31 reported no difference in lymph node retrieval between open and minimally invasive approaches.…”
Section: Discussionmentioning
confidence: 98%
“…Lymph node harvest was not reported by Luketich et al 13 . Smithers and colleagues 31 reported no difference in lymph node retrieval between open and minimally invasive approaches.…”
Section: Discussionmentioning
confidence: 98%
“…Significant respiratory complications are reported to occur in 18-30 % of cases following oesophagectomy and can carry a 50% mortality rate (11)(12)(13)(14) .…”
Section: Pre-operative Feedingmentioning
confidence: 99%
“…44) When one-lung ventilation is used, problems associated with endotracheal tube displacement are also difficult to overcome in the prone position. 17) …”
Section: Possible Disadvantages Of the Prone Position Proceduresmentioning
confidence: 99%
“…20) This procedure was originally performed in the left lateral decubitus position (LLDP). Recent nonrandomized studies have shown a lower rate of major complications than that observed in open surgery; 17,18,21) however, a large systematic review concluded that the actual benefits remain obscure in terms of short-and long-term outcomes. 22) On the other hand, in 1994, Cuschieri 23) first reported the cases of six patients treated with thoracoscopic esophageal mobilization in the prone position (PP).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation